Therapeutic Strategies for SLE Involving Cytokines: Mechanism-Oriented Therapies Especially IFN- Targeting Gene Therapy - Hayashi, Toshiharu (BioMed research international, 2010)
Systemic lupus erythematosus (SLE: lupus) is a chronic complicated autoimmune disease and pathogenesis is still unclear. However, key cytokines have been recognized. Interferon (IFN)- and also IFN are of particular importance. Depending on the concept that lupus is a helper T(Th)1 disease and that dendritic cells (DCs) determine the direction of lupus, balance shift of Th1/Th2 and immunogenic/tolerogenic DCs is reviewed for therapy. (IFN)-- and IFN--targeted (gene) therapies are introduced. These consist of Th1/Th2 balance shift and elimination of IFN- and IFN--related cytokines such as (interleukin)IL-12 and IL-18. Other approaches include suppression of immunocompetent cells, normalization of abnormal T-cell function, costimulation blockade, B lymphocyte stimulator (Blys) blockade, and suppression of nephritic kidney inflammation. Moreover, balance shift of IFN- and tumor necrosis factor (TNF)- together with regulatory T(Treg) cells are briefely introduced. Clinical application will be discussed.